The change of cardiac axis deviation in catheter ablation of verapamil‐sensitive idiopathic left ventricular tachycardia. Issue 4 (17th March 2021) - Sun, Mingyu; Wang, Jian; Wang, Zulu; Liang, Ming; Yang, Guitang; Jin, Zhiqing; Liang, Yanchun; Han, Yaling
Abstract: Background: The underlying mechanism of verapamil‐sensitive idiopathic left ventricular tachycardia (ILVT) has been postulated to be reentrant activation in the Purkinje fiber network of the left posterior fascicle or the left anterior fascicle (LAF). However, changing of cardiac axis deviation in sinus rhythm (SR) or during ILVT after radiofrequency catheter ablation (RFCA) has been rarely analyzed. Methods: Of the 232 patients with sustained ILVT induced and surface electrocardiogram (ECG) in SR recorded before and after RFCA, the changes of ECG morphology in SR and during ILVT were analyzed. Results: The surface ECG in SR changed in 114 (49.1%) patients after RFCA. ILVT could still be induced in 27 (23.7%) patients. In comparison with the original ILVT, three forms of ECG morphology were observed. In eight patients, the ILVT morphology was unchanged. In the 13 patients with ILVT axis deviation conversion after ablation, the successful target was more proximal. In the six patients with ILVT morphology change but without axis deviation conversion after ablation, the successful ablation site was more distal. Among 15 patients with recurrent ILVT during follow‐up, seven patients had previous axis deviation changes in SR after RFCA, the changes maintained in four patients and recovered in three patients. Conclusions: The morphology changes on surface ECG in SR after RFCA would not be a necessary prerequisite or a good endpoint for ILVT ablation. To analyze ILVT morphology changes after ablation would help to further clarify an appropriate approach for catheter ablation of ILVT.